Experimental Investigation of Power-Scaled Dissipative Soliton Generation - Lv, Zhiguo; Yang, Zhi; Li, Feng; Li, Qianglong; Yang, Xiaojun; Wang, Yishan; Zhao, Wei (Frontiers in Physics, 2020)
We conduct a power scaling study for the femtosecond dissipative soliton generation with a 10 m core diameter fiber-based compact-sized and low-cost all-normal-dispersion laser configuration. Laser performance, in terms of spectra distribution, temporal characteristic, average power and stability in 8 h, for different filtering bandwidths has been respectively investigated. In experiment, the obtainable highest output power and shortest pulse duration are 4.5 W and 85 fs, respectively. To our best knowledge this is shortest pulse duration among the reported all-fiber pumped Watt-level mode-locked fiber lasers.